No-tillage in organic production system: production parameters and biomass decomposition - Rocha, Lucas Vasconcelos; Biassi, Dérique; Zonta, Everaldo; Pereira, Marcos Gervasio; Ribeiro , Júlio César (Comunicata Scientiae, 2021)
Soils of sandy texture in the first layers are of great occurrence throughout Brazil. Because of its fragility, it is essential to use crop practices, such as the adoption of a no-tillage system, to promote benefits to these soils. The objective of this study was to evaluate biomass production, nutrient accumulation, decomposition rates, half-life time and dynamics of the N, P and K release of cover crops residues in organic vegetables cropping on no-tillage system in Seropédica-RJ. The experiment was conducted using a randomized block design with multiple replicates and six fractions: crotalaria (Crotalaria juncea), forage peanuts (Arachis pintoi), brachiaria (Brachiaria brizantha), millet (Pennisetum americanum), a cocktail of seeds, and an area of spontaneous vegetation. Dry matter decomposition and nutrient release were evaluated at 15, 30, 60, 90 and 120 days by the litter-bags method. Crotalaria presented higher dry mass production (15.48 Mg ha-1). The legumes had the highest N contents, being the largest values in the crotalaria. For K, the crotalaria also presented the highest values. In relation to decomposition and nutrient release the millet presented the highest half-life time (98 days), while the peanut presented the lowest (23 days).